2021
DOI: 10.1007/s11357-021-00471-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibody and T cell responses elicited by BBIBP-CorV (Sinopharm) and BNT162b2 (Pfizer-BioNTech) vaccines against SARS-CoV-2 in healthy adult humans

Abstract: In the present study, humoral and T cell-mediated immune responses elicited by BBIBP-CorV (inactivated virus) and BNT162b2 (mRNA-based) vaccines against SARS-CoV-2 virus were compared. Convalescent volunteers were also investigated to evaluate adaptive immunity induced by live virus. Although both vaccines induced antibody- and T cell-mediated immune responses, our analysis revealed significant quantitative and qualitative differences between the two types of challenges. The BBIBP-CorV vaccine elicited antirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
48
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 23 publications
22
48
1
2
Order By: Relevance
“…We found BBIBP-CorV boosting poorly induced IGRA response; however, it is important to note that inactivated vaccine (i.e. BBIBP-CorV) may have other antigens (i.e., M or N proteins) that induce T cell responses [36], whereas in our study, we only examined T cell responses to S protein, and thus may have underestimated the cellular responses. The low T cell boosting responses following homologous boosting regimen of ChAdOx1 is in line with the low neutralizing antibody boosting responses observed in this study.…”
Section: Discussionmentioning
confidence: 85%
“…We found BBIBP-CorV boosting poorly induced IGRA response; however, it is important to note that inactivated vaccine (i.e. BBIBP-CorV) may have other antigens (i.e., M or N proteins) that induce T cell responses [36], whereas in our study, we only examined T cell responses to S protein, and thus may have underestimated the cellular responses. The low T cell boosting responses following homologous boosting regimen of ChAdOx1 is in line with the low neutralizing antibody boosting responses observed in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Fu performed an extensive analysis on a small number of patients [ 47 ] but did not report data by age, and all subject was below 60. The antibody and T cell response study of Vályi-Nagy et al was carried out in Hungary just as ours [ 48 ], but unfortunately included almost no elderly subjects. This study, however, did find cellular response even with the Sinopharm vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the authors concluded that both vaccines were capable of eliciting T cell responses but the Pfizer vaccine elicited a stronger but narrower response. 27 These findings of T cell responses by the Sinopharm vaccine were further confirmed in another study. 28 In a study assessing T cell responses in the two mRNA vaccines (Pfizer and Moderna), it was found that both the vaccines showed broad T cell responses to the SARS CoV-2 spike protein which were able to effectively recognize variants of the SARS CoV-2 virus as well as the ancestral virus, providing cross-protection.…”
Section: T Cell Responsesmentioning
confidence: 60%